A Comprehensive Review on Hot Deformation Behavior of High-Entropy Alloys for High Temperature Applications - Jain, Reliance; Jain, Sandeep; Nagarjuna, Cheenepalli; Samal, Sumanta; Rananavare, Anuja P.; Dewangan, Sheetal Kumar; Ahn, Byungmin (Metals and Materials International, 2025)
In contrast to conventional alloys, multicomponent high-entropy alloys (HEAs) have emerged as promising candidates in the field of advanced materials because of their unique composition, microstructure, mechanical and thermal properties, rendering these materials well-suited for a diverse range of applications. For high temperature applications, understanding the hot workability of HEAs is essential for optimizing their processing conditions, tailoring their microstructures and mechanical properties. The current review provides a comprehensive overview of the hot workability of HEAs, including the compression phenomenon observed during hot deformation, the application and use of processing maps, modeling approaches for predicting flow stress, and the deformation mechanisms involved. Different design strategies applicable to HEAs for high-temperature applications have been discussed in this review. The prediction of hot deformation behaviors and processing maps of different HEAs can benefit the research community in designing and developing HEAs for high-temperature applications. Furthermore, we highlight the future scope and challenges in this field.
Keywords: Computational materials; Conventional alloys; High entropy alloys; High-temperature application; Hot deformation behaviors; Hot workability; Integrated computational material engineering approach; Machine-learning; Material engineering; Processing maps; High entropy alloys; High temperature applications; Hot deformation behavior; Integrated computational materials engineering approach; Machine learning